A Conceptual Framework for Approaches to Art Therapy Research in Paediatric Hematology/Oncology Settings (Un cadre conceptuel pour des approches de recherche en art-thérapie en milieu d'hématologie/oncologie pédiatrique). Issue 2 (3rd July 2019) - Kaimal, Girija; Councill, Tracy; Ramsey, Kristin; Cottone, Carrie; Snyder, Kathryn
Abstract: In this viewpoint paper, we present a conceptual framework for research on art therapy with children/adolescents diagnosed with cancer or blood disorders, their families, and healthcare providers. The framework was developed based on the authors' extensive clinical experience with the pediatric hematology/oncology population, observations of mechanisms of change through the art therapy process, current literature based on the biological, psychological, social, and spiritual effects of art therapy with the pediatric hematology/oncology population, and identified gaps in research. The purpose of the conceptual framework, referred to as pediatric care and art therapy study (P-CATs) is to serve as a guide for future research studies and to further understand how art therapy serves the pediatric hematology/oncology population, their families, and healthcare providers.